The determinant factors of the failure of provision of very low-cost housing in Botabek between 1994 and 1996 - 305283 Panangian Simanungkalit (Sekudai : UTM, 1996)
Thesis (Master of Science (Property Management and Valuation)) - Universiti Teknologi Malaysia, 1996